Research on Lateral Bearing Behavior of Spliced Helical Piles with the SPH Method - Guofeng Ren; Yuxing Wang; Yanqin Tang; Qingxu Zhao; Zhiguo Qiu; Wenhui Luo; Zilong Ye (Applied Sciences, 2022)
The length of a spliced pile is 2 m assembled from an original spiral pile using a connector. The whole pile is the structure of the upper straight pipe and the lower spiral. The pile–soil model is established with FEM-SPH by LS-DYNA to simulate and analyze the characteristics of the spliced piles. When the helical pile is subjected to a horizontal load, the pile rotates around the point of rotation, and the contact force position of the soil in the model is as expected. During the process of pile driving, the soil forms an inverted cone stress-area, and the maximum particle stress area near the pile tip and the ground surface is 400 Kpa, which is highly concentrated. When loaded laterally, the area of the interaction stress of the soil particles is divided into three regions: the stress effect region; the transition region; and the critical region. Then, 7° is defined as the ultimate horizontal bearing-capacity of the spliced pile, and the numerical simulation of the horizontal bearing-capacity fundamentally matches the test results. The simulation model realizes the transition from the pile installation to the lateral loading, predicts the ultimate horizontal bearing-capacity, and analyzes the stress distribution of the soil particles and the time-development of the soil displacement.